2000
DOI: 10.1177/13670069000040010601
|View full text |Cite
|
Sign up to set email alerts
|

“Elective affinities”: Language contact in the abstract lexicon and its structural consequences

Abstract: This paper investigates how and what properties of abstract lexical entries in the mental lexicon interact with the distribution of surface morphemes in language contact and/or L1 attrition. Data from Hungarian/English bilingual children provide evidence that asymmetries in the production of Hungarian preverbs and case suffixes may be explained by considering how these morphemes are elected in language production. Effects of differential election and status of “early” versus "late” system morphemes interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…The validity of this assumption will also be addressed in the paper. Various studies have found data which diverge from these constraints (e.g., Backus 2014;de Bot 2004;Zabrodskaja and Verschik 2015), but the constraints have been found in other studies to describe code-switching behaviour well in various contexts (e.g., Deuchar 2006;Deuchar et al 2007;Myers-Scotton 2005), including studies of children (Bolonyai 2000;Paradis et al 2000;Vihman 1998).…”
Section: Constraints On Code-switchingmentioning
confidence: 95%
See 2 more Smart Citations
“…The validity of this assumption will also be addressed in the paper. Various studies have found data which diverge from these constraints (e.g., Backus 2014;de Bot 2004;Zabrodskaja and Verschik 2015), but the constraints have been found in other studies to describe code-switching behaviour well in various contexts (e.g., Deuchar 2006;Deuchar et al 2007;Myers-Scotton 2005), including studies of children (Bolonyai 2000;Paradis et al 2000;Vihman 1998).…”
Section: Constraints On Code-switchingmentioning
confidence: 95%
“…Indeed, studies have shown developmental changes in code-switching behaviour, such as a decline in the proportion of "function words" (variously defined) after the earliest multiword utterances (Meisel 1994;Vihman 1985) and a decline in violations of grammatical constraints during the first few years of language use (Paradis et al 2000); Deuchar and Vihman (2005) found more predicate than argument language mismatches in the first six months of word combinations. Bolonyai (2000), while investigating bilingual children with Hungarian and English, found that the use of both Hungarian and English-influenced structural frames occurred in utterances with and without code-switching, showing language interaction and attrition.…”
Section: Bilingual Children's Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most studies on child L1 attrition report evidence of L1 attrition (Bolonyai 2000;Isurin 2000;Kaufman 1991;Schmitt 2001;Seliger 1996;Tomiyama 2000;Yukawa 1997), there is disagreement as to whether reported child L1 attrition is confounded by incomplete L1 acquisition due to a lack of L1 input in a predominantly L2 environment (Kö pke 2004;Schmid 2004;Schmid and de Bot 2004;Sorace 2004;Yȃgmur 2004). Although the L1 system of adult L2 learners is considered to be more stable, studies find their L1 system is also affected by attrition (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…Eines der ertragreichsten aber auch umstrittensten Modelle, das sich mit grammatischen Einschränkungen beim insertierenden Code-mixing beschäftigt, stellt das Matrix Language Frame-Modell (im Weiteren MLF) von Myers-Scotton (1993;2002) dar (angewendet u. a. bei Backus 1996;Schmitt 2000;Haust 1995;Bolonyai 2000). Das genannte Modell leistete einen bahnbrechenden Beitrag der Untersuchung des Code-mixing insofern, als es auf der Suche nach Regeln des insertierenden Code-mixing im Gegensatz zu früheren Ansätzen nicht die Sprachoberflächenstrukturen zugrundelegt, sondern sich vorrangig auf die Erkenntnisse der Sprachproduktion stützt.…”
Section: Introductionunclassified